Species distribution modeling and phenotypic diversity reveals collection gap in the Musa balbisiana germplasm conservation in Philippines (Asian Journal of Agriculture, 2020)
Abstract. Rabara RC, Sotto RC, Salas EAL. 2020. Species distribution modeling and phenotypic diversity reveal collection gap in the Musa balbisiana germplasm conservation in Philippines. Asian J Agric 4: 71-82. Musa balbisiana is one of the progenitors of cultivated bananas. Its conservation is crucial because of its important phenotypic traits for breeding and genetic improvement of future Musa crops. In the Philippines, the largest ex-situ germplasm collection of M. balbisiana was characterized to assess their phenotypic diversity. Diversity analyses of the 97 plant samples revealed high diversity in the collection. Of the 80 quantitative traits that showed diversity, 51% showed high diversity indices (H?=0.76 to 0.99) while 20% and 29% of the traits have medium and low diversity, respectively. Nineteen percent of the scored morphological traits were invariants, which may reflect the need to increase diversity in the germplasm holdings. Species distribution analysis revealed that annual mean temperature and annual precipitation influenced the species distribution models suggesting the importance of these two environmental factors to species establishment. Overall, phenotypic diversity analyses and species distribution models revealed gaps in the collection. Further collection trips are recommended to increase diversity on traits with low diversity indices and to increase representative accessions from southern Philippines.
Keywords: Crop wild relatives, correlation, ex situ conservation, SDM ensemble, morphological traits